Analytical approaches for the evaluation of data deficient simulated leachable compounds in ENDS products: a case study - Smith, Cameron; Lyndon, Matthew; Jeong, Lena; Lehman, Danielle; Jameson, J. Brian; Chevva, Harish; Ayala-Fierro, Felix; Cook, David; Carter, Karen; Oldham, Michael; Gillman, I. Gene (Frontiers in Chemistry, 2023)
Leachable investigations are routinely undertaken across a range of sectors (e.g., pharmaceuticals, medical devices, etc.) to determine whether chemicals from a container closure system transfer into a product under normal conditions of use. For Electronic Nicotine Delivery Systems (ENDS) the container closure system includes all materials in contact with the e-liquid that is aerosolized and subsequently inhaled by the user. Currently, there is no guidance for conducting leachable studies for ENDS products, however, there are relevant guidance documents for orally inhaled drug products can be applied to an ENDS container closure system. We present a case study of the analytical investigation of two leachable compounds identified in simulated leachable studies using aged JUULpods filled with unflavored e-liquid (PG/VG/nicotine/benzoic acid). Both compounds had limited toxicological information and were considered data deficient. A qualitative analysis of the aerosol collected from aged commercial JUULpods (Virginia Tobacco and Menthol), using a similar analytical method (LC-MS/MS) used in the simulated leachable studies, showed no trace or detectable levels of either leachable compound. Therefore, this qualitative analysis did not provide semi-quantitative values for the data-deficient leachable compounds necessary to support toxicological risk assessment. Further, no commercial authentic standards or reasonable synthetic route were available due to the molecular size and structural complexity of the compounds. Instead, method limits were established using an alternative approach to standard ICH guidelines. The experimentally determined method limit of quantitation, using spiked samples of simulated leachable e-liquid, provided conservative semi-quantitative values for each data deficient leachable compound in the aerosol that enabled a transfer efficiency from e-liquid to aerosol to be estimated. The transfer efficiency of each leachable compound was experimentally determined to be less than 2% based on the limit of quantitation, which then could be used to define a relevant exposure limit for the toxicological risk assessment. This work details a novel analytical approach for determining the transfer efficiency of data deficient leachable compounds from ENDS container closure systems into the ENDS aerosol to support toxicological health risk assessments.